2013
DOI: 10.14236/jhi.v21i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of howRU and EQ-5D measures of health-related quality of life in an outpatient clinic

Abstract: This paper reports on a head-to-head study of howRU and EQ-5D on patients with cardiovascular disease. howRU is a short generic measure of health-related quality of life comprising 39 words, designed for routine use, which we compare with EQ-5D (230 words). Patients attending a clinic completed both instruments. Completed data were available for 116 patients, 51% female, mean age 56 and SD 20. howRU is shorter, has better readability statistics, a higher completion rate, a wider range of states used and a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…In a previous paper, [ 14 ] we compared and discussed the differences between howRu and EQ-5D in a study of the same population. That study showed that howRu is shorter, has better readability statistics, a higher completion rate, used a wider range of states and has a smaller ceiling effect than EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper, [ 14 ] we compared and discussed the differences between howRu and EQ-5D in a study of the same population. That study showed that howRu is shorter, has better readability statistics, a higher completion rate, used a wider range of states and has a smaller ceiling effect than EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared howRu with SF12 [ 6 ] and with EQ-5D [ 14 ], and show that howRu has comparable overall performance at a single point in time. HowRu is considerably shorter than EQ-5D with 37 words vs. 230 words and has been validated for use at the individual patient level [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These assessments included the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) as a measure of current disease activity (Figure 2),16 healthrelated quality of life was monitored via howRu (; four components: pain or discomfort, feeling low or worried, limited in what you can do and require help from others) and physical activity via the validated short form of the International Physical Activity Questionnaire (IPAQ; ), which assesses physical activity frequency, intensity and duration. The howRu questions have better readability statistics and a similar overall performance when based on a single point in time compared with the longer SF1217 and EQ-5D 18. Additionally, an open text question was added to the IPAQ to capture the different activity types patients were undertaking.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison with the EQ5D, the howRu is shorter, has a higher completion rate and a smaller ceiling effect [23]. However, relatively little is known about specific psychometric properties of this instrument, such as the minimal clinical important difference (MCID) which indicates clinically relevant differences.…”
Section: Discussionmentioning
confidence: 99%